2005
DOI: 10.1364/opex.13.003737
|View full text |Cite
|
Sign up to set email alerts
|

Design study of highly sensitive nanowire-enhanced surface plasmon resonance biosensors using rigorous coupled wave analysis

Abstract: In this study, we investigated the sensitivity enhancement in nanowire-based surface plasmon resonance (SPR) biosensors using rigorous coupled wave analysis (RCWA). The enhancement, enabled by the excitation of localized surface plasmons in gold nanowires, offers improved performance in sensitivity as well as in reproducibility and customizability. Calculation results found that a T-profile provides higher sensitivity than an inverse T-profile in general and also determined optimum design parameters. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 24 publications
2
71
0
2
Order By: Relevance
“…For a T-profile, both dominantly excited LSP modes and the structure effect that incurs relatively small interference between substrate and nanowires lead to great improvement of sensitivity. 24 For an inverse T-profile, however, LSPs are not resonantly excited as the strong interaction with a substrate results in damping of LSP modes. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a T-profile, both dominantly excited LSP modes and the structure effect that incurs relatively small interference between substrate and nanowires lead to great improvement of sensitivity. 24 For an inverse T-profile, however, LSPs are not resonantly excited as the strong interaction with a substrate results in damping of LSP modes. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6,14,16,17,23 In our previous study, nanowire-mediated localized SPR biosensors were found to offer significant enhancement in sensitivity, mainly induced by resonantly excited LSPs and LSP-SPP interactions. 24 However, only angular shift of resonance was employed as a metric for the calculation since it was the most conveniently available, so that the structure optimized for maximum sensitivity enhancement was in fact suboptimal from functional aspects of a biosensor. In this paper, we investigate an SPR biosensor structure, in which excitation of and interactions with LSPs are mediated by nanowires, and extend the analysis based on comprehensive design metrics, other than sensitivity enhancement induced by resonance angle shift, such as variations of MRR and SPR CAW.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical calculations using rigorous coupled-wave analysis [38,39] and a finite-difference time-domain (FDTD) method have presented interesting LSPR sensing characteristics of 1D nanogratings built on the flat surface. Byun et al showed that the enhancement enabled by the excitation of LSP modes in gold nanogratings, offers improved performance in sensitivity by more than an order of magnitude compared with a conventional SPR configuration [40]. Optimal gold nanogratings were then designed in terms of the robustness to fabrication errors in implementing periodic structures and the various sensor performances, such as SPR angle shift, SPR curve angular width, and minimum reflectance at resonance [41].…”
Section: Periodic Nanostructure-based Lspr Biosensorsmentioning
confidence: 99%
“…The use of colloidal Au as a nanoparticles tag for the detection of DNA hybridization has shown great improvement in the sensitivity compared to those without Au (He et al 2000). The use of localized surface plasmon resonance (LSPR) to enhance the sensitivity of the waveguides for biosensors has also been addressed (Byun et al 2005;Kim et al 2006). A low propagation loss can be achieved by exhibiting the long-range surface plasmon polarition (LR-SPP) in thin gold stripes embedded in polymer (Nikolajsen et al 2003).…”
Section: Introductionmentioning
confidence: 99%